Synthesis and characterization of a new pyrrolidine containing sulfur ligand and the transition metal complexes of Co(II), Ni(II) and Cu(I) - Gorgulu, Ahmet Orhan; Arslan, Mustafa; Cil, Erol (Taylor & Francis Ltd, 2006)
Potassium 1,3-dipyrrolidinopropan-2-O-xanthate (LK), and its complexes with Co(II), Ni(II) and Cu(I) have been prepared and characterized as [CoL2(H2O)(2)] center dot 2H(2)O, [NiL2(H2O)(2)] and CuL center dot 2H(2)O by FT-IR, H-1 and C-13 NMR spectroscopies, elemental analyses, magnetic susceptibility and TGA techniques.
Keywords: Co(II); Ni(II); Cu(I) complexes; xanthate